2009
DOI: 10.1097/inf.0b013e31819f1f89
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Viruses Associated With Hospitalization Due to Lower Respiratory Tract Infections in Canadian Inuit Children

Abstract: Smoking during pregnancy, place of residence, Inuit race, lack of breast-feeding, and overcrowding were all independently associated with increased risk of hospital admission for LRTI among Inuit children less than 2 years of age. Future research on the role of adoption and genetics on the health of Inuit children are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
74
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 29 publications
4
74
0
Order By: Relevance
“…However, it is still a concern in Northern Canada with a substantially higher rate among Indigenous infants. Some studies suggested that poor health, environmental and housing conditions of Indigenous children may be potential risk factors (28)(29)(30)(31). Hia has been a predominant serotype in Northern Canada since the beginning of ICS (5,22,32), whereas non-typaeble Hi and type f are more common in other circumpolar regions (32).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is still a concern in Northern Canada with a substantially higher rate among Indigenous infants. Some studies suggested that poor health, environmental and housing conditions of Indigenous children may be potential risk factors (28)(29)(30)(31). Hia has been a predominant serotype in Northern Canada since the beginning of ICS (5,22,32), whereas non-typaeble Hi and type f are more common in other circumpolar regions (32).…”
Section: Discussionmentioning
confidence: 99%
“…[121] Etiologic studies of pediatric hospitalizations for acute lower respiratory tract infections have identified influenza to be associated with 2-23% of admissions, with most large studies identifying influenza virus in 5-10% of hospitalized children in both developed and developing countries. [122][123][124][125][126][127][128][129][130][131][132][133][134][135][136][137][138][139][140] Rates of influenza-associated hospitalizations are primarily available from developed countries, where approximately 1-3 hospitalizations per 1000 child-years have been observed. [113,114,117,[141][142][143][144][145] Influenza-associated hospitalization rates are higher among children with cardiac and pulmonary conditions than among healthy children.…”
Section: Disease Burdenmentioning
confidence: 99%
“…In Nunavut, suicide rates are 11 times higher and TB incidence is 62 times greater than the Canadian average, with 100 new active cases of TB documented in 2010 (Health Canada, 2006;MacDonald, Hébert, & Stanbrook, 2011). Lower respiratory tract infections have been found to be the leading cause for the medical evacuation and hospitalization of Inuit children: rates are as high as 48.4% among infants under the age of 6 months (Banerji, 2009). Poor ventilation in overcrowded housing is a primary cause of these illnesses, with about four in 10 Inuit living in overcrowded housing-13 times more than the Canadian average (Tester, 2006).…”
Section: Discussionmentioning
confidence: 99%